Functional Status and Incidence of Loss to Follow-up after Antiretroviral Therapy Initiation - Dewi Ambarwati, Rosita; Eko Wardani, Hartati; Dwi Tama, Tika (KnE Life Sciences, 2021)
Taking medication for lifetime puts Human Immunodeficiency Virus (HIV)-infected patients in challenging situations. The loss to follow-up (LTFU) is a major problem arising from their non-compliance. Information about functional status as a predictor of LTFU is limited. Therefore, this study was aimed to identify the association between the functional status and the incidence of LTFU among HIV patients at Saiful Anwar General Hospital, Indonesia. A retrospective cohort study was conducted in the tropical diseases and infections division of the Saiful Anwar General Hospital by observing 148 HIV patients who were diagnosed in 2015. Data were collected based on existing data in medical records. The log-rank test was used to compare the time of LTFU between groups. Cox proportional hazard was used to determine the effect of functional status after being controlled by other variables. This study found that 65.9% of HIV patients were able to retain on antiretroviral therapy for 39 months. Functional status had a significant association with the time LTFU occurred. Ambulatory patients had a higher risk of experiencing LTFU than working functional status (AHR = 2.289; 95% CI 1.106–4.738; p-value = 0.026). Identifying the patient’s characteristic that has a higher risk of LTFU helps to determine the right strategy to ensure treatment adherence. Keywords: antiretroviral therapy (ART), functional status, HIV, loss to follow-up (LTFU), Indonesia